Relevansi Kausal Motivasi Kerja pada Komitmen Organisasional Karyawan Hotel Betha Subang - Hotmaida Sihombing; Rony Setiawan (Eastasouth Institute, 2023)
After the pandemic, the service industry in the hotel sector has started to show its resilience again. The quality of hotel services provided depends on the performance of the employees who provide them. Betha is one of the leading hotels in Subang which shows an employee retention rate of more than 85% in the midst of rampant layoffs that occur. Organizational commitment has a very crucial role for the stability and progress of the company, which is caused by employee motivation. Through the interview process, literature review, and a questionnaire with 25 items of questions, this research aims to confirm the causality of motivation on organizational commitment, both in terms of variables and dimensions. By involving all employees who work at Hotel Betha Subang, this research proves that motivation affects affective commitment, continuance commitment, normative commitment, and organizational commitment. Researchers hope that this research can be a theoretical and practical inspiration for the development of knowledge and the creation of positive work.